Conceptual principles and theoretical basis of innovative activity in the modern construction industry - Ivakhnenko, I.S.; Koval, I.A.; Grogol, V.Ya.; Makeev, D.S.; Kryvda, K.E. (Ways to Improve Construction Efficiency, 2023)
The construction industry is one of the key sectors of the economy, which largely determines the level of development of infrastructure, the social sphere and the industrial potential of the state. In the context of globalization, rapid technological progress and growing environmental challenges, the relevance of innovative activity in the construction sector is constantly growing. The introduction of new technologies, materials, methods of design and management of construction processes is an integral part of the sustainable development of the industry, which allows to improve the quality, safety, efficiency and environmental friendliness of construction. The conceptual principles of innovative activity cover comprehensive approaches to the creation, implementation and use of new technologies and materials that contribute to the optimization of construction processes. An important task is to harmonize scientific and technological progress with economic and environmental aspects. The introduction of modern digital technologies, such as BIM (Building Information Modeling), automation of construction processes, the use of artificial intelligence and "smart" construction solutions, significantly changes traditional approaches to the design, construction and operation of facilities. The theoretical foundations of innovation in the construction industry are based on an interdisciplinary approach that combines engineering, economic, managerial and environmental aspects. Analysis of innovation processes allows us to identify key success factors, including financial support, research and development, legal regulation, international experience and professional training. Improving the regulatory framework and stimulating investment in scientific and technical development are important conditions for the formation of a favorable environment for innovation in construction. Thus, the study of the conceptual foundations and theoretical foundations of innovation in the modern construction industry is of strategic importance. The introduction of innovations not only increases the competitiveness of the construction industry, but also contributes to the development of sustainable construction, which meets global trends and requirements of modern society.